Coping behaviour of rural inhabitants against COVID-19 and monsoon flood: evidence from Bangladesh. Issue 2 (17th February 2022) - Baser, Shahadat; Nazem, Nurul Islam; Ahmad, Mokbul Morshed; Hasnath, Syed Abu
ABSTRACT: This research aims to identify the impact of COVID 19 and monsoon floods on rural Bangladesh communities and assess their coping behaviour. Data were collected through an in-depth study. The findings reveal that char(shoal) dwellers and riverbank communities were more affected due to unexpected floods than coronavirus infections with poor access to health, less knowledge of hygiene, no risk reduction measures, or any suitable coping strategies. Furthermore, the result shows that traditional livelihood sources like fishing, ferrying passengers by boat, borrowing money from affluent relatives, or food loans, selling livestock, etc., were usual. Local authorities were mostly inactive in alleviating suffering.